4C skills teaching activities for mathematics teachers: application of modified nominal group technique - Zakaria, Mohamad Ikram; Hanri, Chuzairy; Noer, Sri Hastuti; Triana, Mella; Widyastuti, Widyastuti (Journal of Education and Learning (EduLearn), 2025)
Education 4.0 strongly promotes the development of communication, collaboration, critical thinking, and creativity (4C) skills among students. Consequently, it is crucial for mathematics teachers to integrate activities that facilitate the cultivation of these skills. However, the scarcity of resources, such as recommended instructional activities, poses a challenge for mathematics teachers striving to effectively impart 4C skills through problem-solving methods. This research aims to develop a set of teaching activities designed to enhance the delivery of 4C skills through problem-solving methods, thereby supporting mathematics teachers in improving their pedagogical strategies. Utilizing the modified nominal group technique (mNGT), the study engaged 11 experts from diverse fields, including mathematics education, pedagogy, curriculum development, and primary and secondary education. Data collection was conducted through expert discussions between January 2024 and February 2024. Descriptive statistics (percentages) were employed to analyze the data, prioritizing and ranking each teaching activity. The findings identified 19 pertinent teaching activities that emphasize 4C skills through problem-solving methods. The highest-ranked activity was motivating students to explore various learning resources, including information and communication technology (ICT) tools (98%), while guiding students through problem-solving questions received the lowest ranking (75%). In conclusion, the comprehensive list of teaching activities provides a valuable guide for mathematics teachers to effectively incorporate 4C skills into their instructional practices.